Specific features of the oxidation of a tungsten nanopowder; Russian Journal of Physical Chemistry A; Vol. 78, № 9 - Gromov A. A.; Kwon Y. S.; Ilyin A. P. Aleksandr Petrovich; Vereshchagin (Vereschagin, Vereshagin) V. I. Vladimir Ivanovich (2004, 2004)
The mechanism and products of the passivation in air of a tungsten powder (as - 100 nm) prepared by the electroexplosion technique was studied. The oxidation of tungsten nanoparticles was demonstrated to occur via several stages and involve W3O, the lowest oxide. The products of the oxidation of the tungsten nanoparticles were examined by transmission electron microscopy, X-ray photoelectron spectroscopy, XRD analysis, DTA-TG thermal analysis, and high-resolution transmission microscopy. A reaction scheme of the oxidation of tungsten nanoparticles in air is proposed.